Delivery of stable ultra-thin liquid sheets in vacuum for biochemical spectroscopy - Barnard, Jonathan C. T.; Lee, Jacob P.; Alexander, Oliver; Jarosch, Sebastian; Garratt, Douglas; Picciuto, Rose; Kowalczyk, Katarzyna; Ferchaud, Clement; Gregory, Andrew; Matthews, Mary; Marangos, Jon P. (Frontiers in Molecular Biosciences, 2022)
The development of ultra-thin flat liquid sheets capable of running in vacuum has provided an exciting new target for X-ray absorption spectroscopy in the liquid and solution phases. Several methods have become available for delivering in-vacuum sheet jets using different nozzle designs. We compare the sheets produced by two different types of nozzle; a commercially available borosillicate glass chip using microfluidic channels to deliver colliding jets, and an in-house fabricated fan spray nozzle which compresses the liquid on an axis out of a slit to achieve collision conditions. We find in our tests that both nozzles are suitable for use in X-ray absorption spectroscopy with the fan spray nozzle producing thicker but more stable jets than the commercial nozzle. We also provide practical details of how to run these nozzles in vacuum.